Perencanaan Pengendalian Persediaan Bahan Baku Ayam Fresh Menggunakan Metode MRP (Material Requirement Planning) Pada PT. Raja Jeva RPA Nusantara - Dahniar, Tedi; Swara , Muhamad Rendika (JITMI (Jurnal Ilmiah Teknik dan Manajemen Industri), 2025)
PT Raja Jeva Nisi RPA Nusantara is a chicken slaughtering company whose production process starts from live chickens to high-quality products such as Fresh chicken carcasses, broiler chicken, Frozen food, and other processed chicken products. In the production process there is an excess of Fresh chicken raw materials in May 2024 of 590 heads which are allocated to the warehouse to be produced at a later date which causes a buildup of Fresh chicken raw materials and increased inventory costs. The purpose of this study is to determine the level of demand for Fresh chicken in accordance with market needs and to determine the planning of inventory control of fresh chicken raw materials in increasing cost efficiency at PT Raja Jeva Nisi RPA Nusantara. Then the results of forecasting to determine the level of demand for fresh chicken for 1 year, namely November 2023 to October 2024 amounting to 129,470 fresh chickens. Then, the second step is the calculation of safety stock to facilitate production activities, the proposed safety stock given to PT Raja Jeva Nisi RPA Nusantara is a service level of 95% of 952 heads / month and the reorder point of fresh chicken is carried out when the amount of inventory in the warehouse has reached the level of 11,850 heads for a service level of 95%. While the results of the calculation of lot sizing techniques in planning raw material inventory control obtained the most efficient total cost of Rp. 37,006,752 with the POQ method.